International equity portfolio investment and enforcement of insider trading laws: a cross-country analysis - Kwabi, Frank O.; Boateng, Agyenim; Adegbite, Emmanuel (Springer, 2018)
In this study, we examine the effects of stringent insider trading laws’ enforcement, institutions and stock market development on international equity portfolio allocation using data from 44 countries over the period 2001-2015. Our results suggest that stringent insider trading laws and their enforcement exert a positive and significant impact on international portfolio investment allocation. Further analysis indicates that the interaction between a country’s institutional quality, stock market development and enforcement of insider trading laws have a positive and significant effect on international equity portfolio allocation. The findings of this study have implications for the design of portfolio investment trading strategies and contribute to the literature on foreign equity investment decisions.